(untitled) (Economics and region, 2021)
An analysis of land transformations, transformations and reforms in the world and in Ukraine, in particular, has been introduced. Eight historical periods of land relations in Ukraine are considered: the first - ancient times; the second - the period of Kievan Rus; third - the Polish-Lithuanian period; fourth - the Cossack state and the Hetmanate; fifth - joining the Russian and Austrian empires; sixth - 1917 - 1920 - land revolutionary transformations (UPR); seventh - the period of the USSR; the eighth is the state of Ukraine. The fact is taken into account that the content of economic relations of land ownership consists of possession, use and disposal of land rent, and certain rights to land resources. The stages of development of land relations are mainly related to changes in economic relations, land ownership relations and development for their use in various sectors of economic activity. In all social formations, land management is carried out in the interests of the ruling classes. Historically, land management has changed depending on the replacement of some exploiting classes with others. The essence of land management for each given historical method of production is determined by economic relations. Historically, land reform in Ukraine is aimed at transforming state and collective property into private and forming on its basis a more effective socio-economic system of relations with a high motivational mechanism to work with a stable system of responsibility for its results.